Analisis Peranan Ekonomi dan Menggunakan Pendekatan Pemangku Kepentingan (Stakeholders) - Khoirinnisa, Prima; Nurrohmah, Laili; Sarpini, Sarpini (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research aims to analyze the role of economics and business in the context of sustainable development using a stakeholder approach. In facing complex global economic challenges, collaboration between various stakeholders—including government, the private sector, and society—has become critical to creating solutions that are effective and responsive to society's needs. The research method applied is descriptive qualitative, with data collection through in-depth interviews and participant observation in locations with significant economic activity. The research results show that synergy between stakeholders has a big influence on local economic development. This research identifies key factors such as effective communication and trust as important elements in collaboration. It is hoped that these findings will provide insight for policy makers and business people in formulating more inclusive and sustainable development strategies.